Morphological evaluation of gonial and antegonial regions in bruxers on panoramic radiographic images - Zerrin Unal Erzurumlu; Elif Sadik; Busra Nur Gokkurt; Furkan Ozbey; Kerem Erzurumlu; Yeliz Kasko Arici (BMC, 2023)
Abstract Background This is the first study to report both cortical and trabecular bone evaluation of mandibles in bruxers, within the knowledge of the authors. The purpose of this study was to evaluate the effects of bruxism on both the cortical and the trabecular bone in antegonial and gonial regions of the mandible, which is the attachment of the masticatory muscles, by using panoramic radiographic images. Methods In this study, the data of 65 bruxer (31 female, 34 male) and 71 non-bruxer (37 female, 34 male) young adult patients (20-30 years) were evaluated. Antegonial Notch Depth (AND), Antegonial-Index (AI), Gonial-Index, Fractal Dimension (FD) and Bone Peaks (BP) were evaluated on panoramic radiographic images. The effects of the bruxism, gender and side factors were investigated according to these findings. The statistical significance level was set atP ≤ 0.05. Results The mean AND of bruxers (2.03 ± 0.91) was significantly higher than non-bruxers (1.57 ± 0.71; P < 0.001). The mean AND of males was significantly higher than females on both sides (P < 0.05). The mean AI of bruxers (2.95 ± 0.50) was significantly higher than non-bruxers (2.77 ± 0.43; P = 0.019). The mean FD on each side was significantly lower in bruxers than in non-bruxers (P < 0.05). The mean FD of males (1.39 ± 0.06) was significantly higher than females (1.37 ± 0.06; P = 0.049). BP were observed in 72.5% of bruxers and 27.5% of non-bruxers. The probability of existing BP, in bruxers was approximately 3.4 times higher than in non-bruxers (P = 0.003), in males was approximately 5.5 times higher than in females (P < 0.001). Conclusion According to the findings of this study, the morphological differences seen in cortical and trabecular bone in the antegonial and gonial regions of the mandible in bruxers can be emphasized as deeper AND, higher AI, increased of existing BPs, and lower FD, respectively. The appearance of these morphological changes on radiographs may be useful for indication and follow-up of bruxism. Gender is an effective factor on AND, existing BP and FD.